Development of a biology practicum module with microtech-nical preparations on the structure and function of plant tissue - Samsul Arifin; Mohamad Amin; H. Husamah; Atok Miftachul Hudha; Fuad Jaya Miharja (Research and Development in Education (RaDEn), 2021)
There has been no development or preparation of microtechnical modules on the material structure and function of plant tissues equipped with preparations. Therefore, the purpose of this research and development was to produce modules equipped with microtechnical preparations and analyze their quality through validation of teaching materials experts, material experts, and readability by teachers and students on small- and large-scale trials. This type of research was Research and Development (R&D) with the ADDIE development model which has five stages, namely: analysis, design, development, implementation, and evaluation. The results of the development research were in the form of a product of a biology practicum module with microtechnical preparations. The quality of the modules according to the teaching materials experts and materials experts was very good with the percentages of 80.6% and 99.4%, respectively. The result of the teacher's response was 81.4% with a very good category and readability by students on a small and large scale respectively 88% and 82.7%. Based on this assessment, it shows that the module with this preparation was suitable for use as teaching material by teachers in biology learning activities on the structure and function of plant tissue.